2018
DOI: 10.3390/molecules24010052
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired-Metalloporphyrin Magnetic Nanocomposite as a Reusable Catalyst for Synthesis of Diastereomeric (−)-Isopulegol Epoxide: Anticancer Activity Against Human Osteosarcoma Cells (MG-63)

Abstract: In the present study, we developed a green epoxidation approach for the synthesis of the diastereomers of (−)-isopulegol benzyl ether epoxide using molecular oxygen as the oxidant and a hybrid manganese(III)-porphyrin magnetic reusable nanocomposite as the catalyst. High activity, selectivity, and stability were obtained, with up to four recycling cycles without the loss of activity and selectivity for epoxide. The anticancer effect of the newly synthesized isopulegol epoxide diastereomers was evaluated on a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The above cancer cell lines in the exponential growth phase (5000 cells/well) were cultured in 96-well plates for 24 h under optimal conditions (37 °C, 5% CO 2 incubator). 29,30 Then, AMGADs (10 μL) were gently mixed with the cultured cancer cells and incubated at 37 °C for 72 h, and 50% w/v ice-cold trichloroacetic acid was added to fix the cells. After SRB was added for staining, Tris solution (150 μL•well −1 ) was added, and the OD 540 was measured by a microplate reader.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The above cancer cell lines in the exponential growth phase (5000 cells/well) were cultured in 96-well plates for 24 h under optimal conditions (37 °C, 5% CO 2 incubator). 29,30 Then, AMGADs (10 μL) were gently mixed with the cultured cancer cells and incubated at 37 °C for 72 h, and 50% w/v ice-cold trichloroacetic acid was added to fix the cells. After SRB was added for staining, Tris solution (150 μL•well −1 ) was added, and the OD 540 was measured by a microplate reader.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…32 Moreover, it was found in the literature that although (-)-isopulegol benzyl epoxides had inert properties in chemical transformations, 33 they could act as antiproliferative alkylating agents. 34 Consequently, the antiproliferative activity of our compounds was examined. The in vitro cytotoxic activities of the prepared 4-amino-2,3-epoxide-1ol analogues were also investigated against a panel of human malignant cell lines isolated from cervical (SiHA and HeLa), breast (MCF7 and MDA-MB-231), and ovary (A2780) cancers (Figure 3 and SI, Table S2).…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…Results indicated that both diastereomers showed similar in vitro potency. [87] ). [86] (À )-Isopulegol 2 was oxidised to diol 96, [39] which was again converted into both dibenzyl-and monobenzylprotected diols ).…”
Section: Isopulegol-based Bi-and Trifunctional Chiral Compoundsmentioning
confidence: 99%